Classification of Poisonings and Natural Toxins in Iranian Medicine and its Comparison with Modern Classification - Rezaei Orimi, Jamal; Nasiri, Ebrahim; Siamian, Hasan; Moallemi, Mostafa; Balaghafari, Azita; Padashi, Sohrab (Journal of Liaquat University of Medical & Health Sciences, 2022)
Poisoning is an essential public health issue that causes deaths worldwide yearly. This study aims to determine the Classification of poisonings and natural toxins in the Eighth to twelfth centuries AD in Iranian medicine primary sources and compare it with modern medicine. This research is a review study based on the library method. In this study, the terms in Persian and Arabic languages were extracted from the Al-Sumum section of Iranian medicine’s primary sources. Current medical literature (using PubMed, Scopus, Google Scholar, Web of Science, Magiran and SID databases) was also searched with equivalent terms. Then, the obtained results were expressed separately. The results showed that poisoning in Iranian medicine, in terms of entry; includes two categories of gastrointestinal and injectable, based on the type of toxic substance; it consists of three categories; plants, animals, and minerals, based on their habitat: They are divided into two categories; marine and terrestrial, and based on their temperament, they are divided into two categories: hot-tempered and cold-tempered. Poisonous animals such as snakes are divided into three classes: poisonous, semi-venomous and harmless. In modern medicine, the types of poisoning include two kinds of poisoning with medicinal and non-medicinal substances. These recommendations, which result from hundreds of years of experience of Iranian physicians, could be helpful; however, future experimental investigations are needed to approve their safety and efficacy along with the possible mechanisms of action. KEYWORDS: Poisons, Poisoning, Classification, History of Medicine, Medicine, International Classification of Diseases